Role of cancer antigen-125 in diagnosing malignant adnexal masses: a prospective observational study - Khan, Shazia Ashraf; Rahi, Shaista; Khan, Nahida (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Adnexal masses present a diagnostic and therapeutic dilemma across age-groups. This study aimed to evaluate the performance of cancer antigen-125 (CA-125) in distinguishing between benign and malignant adnexal masses. Methods: This was a prospective, observational, single tertiary-care center study, done in North India from January, 2011 till December, 2012. Serum CA-125 levels was obtained preoperatively in consecutive patients presenting with ultrasonography confirmed adnexal masses. The cut-off value between benign and malignant was taken as 35 IU/ml. Histopathological diagnosis was obtained in all patients. Results: A total of 126 patients presented with adnexal masses, of which 100 were enrolled (mean age: 37.5±14.4 years, range: 18-80 years). Most of the masses were benign 81% (malignant=19%). Dermoid cyst (25.9%) and endometriomas (21%) were the most common benign masses. Serous (21%) and mucinous cystadeno-carcinoma (15.8%) were the most common malignant masses, more often seen in elderly, married, parous and post-menopausal patients. Mean CA-125 levels were significantly higher in malignant masses (257.30 [105.68-408.92] versus 19.26 [16.53-22.00], p<0.001). Overall sensitivity, specificity, positive predictive value, negative predictive value and accuracy of CA-125 for diagnosing malignant adnexal mass was 94.7%, 87.65%, 64.28%, 98.6%, and 88.91% respectively. The same was 100%, 85.1%, 54.5%, 100%, 87.3% in premenopausal and 85.7%, 100%, 100%, 93.3%, 95.2% in postmenopausal women respectively. Conclusion: Benign masses form the bulk of the adnexal masses in all age groups. CA-125 levels has high sensitivity and negative predictive value in premenopausal patients while as high specificity and positive predictive value in postmenopausal patients.